Социальный маркетинг: предмет и основные типы - Акимов, Д. (Социология: теория, методы, маркетинг, 2009)
The modern approach to optimization of social processes management in nowadays societies is examined in the article, particularly applying to such transforming count ries as Ukraine. The social marketing understood as a modern technology of social sphere functioning organization is considered as a key approach in this context. The social marketing is characterized, on the one hand, as a socially oriented and deter mining social responsibility of business technology and, on the other hand, as a technology of “promotion” of meaningful social problems. The basic types of the social marketing are described in the article, namely: political marketing, state marketing; territorial marketing and social marketing in the narrow sense of the term (i.e. the education and sport marketing, the marketing in public health and culture spheres, the marketing of ideas and programs, religious marketing etc.). The scientific and practical potential of social marketing conception allows developing the effective approach to scientifically grounded regulation of social processes, solution of social problems, optimization of political activities and state and territorial administration.